INSTITUTIONAL OWNERSHIP MEMODERASI HUBUNGAN TAX HAVEN COUNTRY, MULTINATIONALITY DAN UKURAN KOMITE AUDIT PADA PRAKTIK THIN CAPITALIZATION - Luvito, Andi; Iin Rosini; Suripto (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
The phenomenon of thin capitalization practices in Indonesia revealed by the Directorate General of Taxes and the Tax Justice Network is closely related to international activities and foreign interests carried out by more than two thousand foreign companies in Indonesia and is estimated to cause losses to the state of up to 11 million dollars every year. This study aims to examine and analyze institutional ownership moderating the relationship between tax haven country, multinationality and audit committee size on thin capitalization. The type of research used is quantitative associative. The population in this study are companies that are members of IDX SMC Liquid which are listed on the Indonesia Stock Exchange in 2018-2022 as many as 60 companies. Determined of the sample of this study was carried of through saturated sampling technique and obtained 60 companies for five years so that the number of observation data obtained was 285 data. The data analysis technique uses panel data regression analysis with te help of Eviews version 12 as a measuring tool. The results show that tax haven country and multinationality had a positive effect on Thin Capitalization, audit committee size had no effect on Thin Capitalization, institutional ownership moderates the relationship between tax haven country, multinationality and Thin Capitalization, Institutional Ownership weakens the relationship between Committee Size Audit with Thin Capitalization.